2020
DOI: 10.35241/emeraldopenres.13684.1
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic, psychological response to quarantine, and knowledge of the disease among inmates in a Nigerian custodial center

Abstract: This was a cross-sectional study to assess the psychological response to quarantine during COVID-19 pandemic and the level of knowledge about the disease among inmates of a Custodial Center in Enugu, Nigeria. A total of 66 new prison inmates were assessed for psychological distress using the Kessler Psychological Distress Scale (K10); and inmates’ knowledge about COVID-19 using a COVID-19 Knowledge Questionnaire developed by the researchers. Participants had a mean age of 28.39±8.71 years; 63 (95.5%) were male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
(11 reference statements)
1
5
0
Order By: Relevance
“…Workers of “La Nave” ward have confirmed that an awareness-raising campaign on flu and anti-pneumococcal vaccination is currently underway. It is well known that receiving information about COVID-19 could prevent psychological distress or anxiety ( WHO, 2020 ), whilst a paucity of information can produce high psychological distress for prisoners ( Okoro et al , 2020 ). For “cognitions” an interesting issue was the way detainees evaluated and represented the virus to themselves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Workers of “La Nave” ward have confirmed that an awareness-raising campaign on flu and anti-pneumococcal vaccination is currently underway. It is well known that receiving information about COVID-19 could prevent psychological distress or anxiety ( WHO, 2020 ), whilst a paucity of information can produce high psychological distress for prisoners ( Okoro et al , 2020 ). For “cognitions” an interesting issue was the way detainees evaluated and represented the virus to themselves.…”
Section: Discussionmentioning
confidence: 99%
“…This can be achieved by providing knowledge about what is happening and why, providing meaningful activities, ensuring supplies such as masks, disinfectants and regular sanitizing materials (especially in a context of prison overcrowding) and continuing to provide psychiatric and psychological support. Recent studies underlined the difference in the development of psychological distress between quarantined people in prison and the general population ( Kothari et al , 2020 ; Okoro et al , 2020 ). Okoro et al (2020) observed that the high level of psychological distress among people in prison can stem from a poorer level of knowledge about COVID-19, sometimes associated with lower levels of education compared to the general population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the perception of the respondents about covid-19, majority of them strongly agreed that the disease is real and is a serious disease but not in Nigeria where most of the participants strongly disagreed that people did not die from the disease, know or have seen someone who suffered from the since the disease can be prevented through regular washing of hands with soap, maintaining social distance, wearing of nose mask, cleaning and disinfecting the environment. (32) in their study found that 4/5 of the respondents perceived there are con rmed cases of the disease in Nigeria and other parts the world.…”
Section: In Uence Of Demographic Variables On Compliance To Covid-19 Preventive Measuresmentioning
confidence: 94%
“…With regards quarantined individuals, a study in Enugu, Nigeria proposed that in quarantined individuals, significant knowledge about COVID-19 was lower among those with psychological distress than among those without psychological distress. They suggested that it is essential to constantly educate people before, during and after quarantine [31].…”
Section: The Psychosocial Effect Of the Corona Virus In Africamentioning
confidence: 99%